Sistem Artificial Intelligence Deteksi Penyakit THT dan Jantung Menggunakan Forward Chaining dan Image Processing - Wibowo, Ari Purno Wahyu; Hamdani, Dani; Heryono, Heri; Pratama, Rizky Fajar (Jurnal Ilmiah Informatika Global, 2024)
Heart disease and ENT (Ear, Nose and Throat) disease are serious can threaten human health and even life, the attacks of these two diseases can come suddenly without us realizing it, the symptoms are similar to ordinary diseases, the aim of this research is created based on AI (artificial intelligence) which is able to provide a quick response when a disease attacks us by looking for signs of physical changes or early symptoms in the body, examples of these symptoms are changes in skin color or finger nails which can indicate the presence of a serious disease, the method used is a combination of two detection methods using forward chaining and the heart disease detection system using the image processing method, the application created is able to detect disease symptoms and measure the level of accuracy of the detection results, so that the patient or doctor is able to measure the severity of the disease, from the experimental results it can be concluded that this system can recognize with an accuracy of above 80%, this application doesn't replace the doctor as a medical expert but is used for recognize early symptoms and carry out  prevention processes  disease becomes more serious.